Change in skeletal muscle index and its prognostic significance in patients who underwent successful conversion therapy for initially unresectable colorectal cancer: observational study. (November 2020) - Nozawa, Hiroaki; Emoto, Shigenobu; Murono, Koji; Shuno, Yasutaka; Kawai, Kazushige; Sasaki, Kazuhito; Sonoda, Hirofumi; Ishii, Hiroaki; Iida, Yuuki; Yokoyama, Yuichiro; Anzai, Hiroyuki; Ishihara, Soichiro
Background: Systemic therapy can cause loss of skeletal muscle mass in colorectal cancer (CRC) patients in the neoadjuvant and palliative settings. However, it is unknown how the body composition is changed by chemotherapy rendering unresectable CRC to resectable disease or how it affects the prognosis. This study aimed at elucidating the effects of systemic therapy on skeletal muscles and survival in stage IV CRC patients who underwent conversion therapy. Methods: We reviewed 98 stage IV CRC patients who received systemic therapy in our hospital. According to the treatment setting, patients were divided into the conversion, neoadjuvant chemotherapy (NAC), and palliation groups. The cross-sectional area of skeletal muscles at the third lumbar level and changes in the skeletal muscle index (SMI), defined as the area divided by height squared, during systemic therapy were compared among patient groups. The effects of these parameters on prognosis were analyzed in the conversion group. Results: The mean SMI increased by 9.4% during systemic therapy in the conversion group ( n  = 38), whereas it decreased by 5.9% in the NAC group ( n  = 18) and 3.7% in the palliation group ( n  = 42, p  < 0.0001). Moreover, patients with increased SMI during systemic therapy had a better overall survival (OS) than those whose SMI decreased in the conversion group ( p  = 0.025). The increase in SMI was an independent predictor of favorable OS on multivariate analysis (hazard ratio 0.25). Conclusions: Stage IV CRC patients who underwent conversion to resection often had an increased SMI. On the other hand, a decrease in the SMI during systemic therapy was a negative prognostic factor in such patients.